The role of country governance in value-added tax and inequality - Ramly, Zulkufly; Chan, Sok Gee (Technická univerzita v Liberci, 2018)
Income inequality is a growing concern for regulators because it brings adverse consequences towards social stability, institutional stability, and economic performance. One of the popular ways to reduce income inequality is through the implementation of Value Added Tax (VAT) despite many criticisms on its regressive nature. Hence, using a wide data range from 1984 to 2014, we study the impact of VAT on income inequality in both developed and developing countries. Besides, this is the first study that seeks to focus on the moderating role of country governance in enhancing the effect of VAT on income inequality. We use the Generalized Method of Moments (GMM) to overcome the endogeneity, autocorrelation and heteroscedasticity issues. The results suggest that the VAT reduces income inequality but the positive effect is contingent upon the existence of a set of good country governance. Countries that have a higher quality of bureaucracy, greater democratic accountability, high government stability, effective law and order, low political risk and favourable socioeconomic conditions stand to benefit more from the VAT system in terms of narrowing the income inequality. Therefore, we conclude that better institutions improve the tax collection and public service delivery, which is a crucial element in achieving the economic objective of narrowing the income gap between the wealthy and the poor. This is particularly true in developing countries. Further, the governments in developing countries need to effectively manage the degree of socioeconomic pressure that could distract them from implementing social and economic policies to eradicate poverty and raise the income level of the poor segment of society.